2021
DOI: 10.1590/0004-282x-anp-2020-0243
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure behavior during mechanical thrombectomy and drugs used for conscious sedation or general anesthesia

Abstract: Background: The optimal blood pressure (BP) during mechanical thrombectomy for acute ischemic stroke is currently unclear. Objective: To investigate BP behavior during mechanical thrombectomy in patients with acute ischemic stroke and its relationship with drugs used for sedation or general anesthesia. Additionally, we investigated the association between BP oscillation during mechanical thrombectomy and recanalization status, and with functional outcome at discharge. Methods: Consecutive patients treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Despite the higher incidence of pneumonia in the GA group compared to the CS group, our study found that even within the CS group, 17% of patients developed pneumonia. Some commonly used CS-related anesthetic drugs, such as neuromuscular blocking agents, may increase the risk of patients developing pneumonia because they can lead to respiratory muscle paralysis and the risk of aspiration (39). Therefore, the incidence of pneumonia cannot be ignored when EVT is administered under either anesthetic.…”
Section: Figurementioning
confidence: 99%
“…Despite the higher incidence of pneumonia in the GA group compared to the CS group, our study found that even within the CS group, 17% of patients developed pneumonia. Some commonly used CS-related anesthetic drugs, such as neuromuscular blocking agents, may increase the risk of patients developing pneumonia because they can lead to respiratory muscle paralysis and the risk of aspiration (39). Therefore, the incidence of pneumonia cannot be ignored when EVT is administered under either anesthetic.…”
Section: Figurementioning
confidence: 99%
“…Por el contrario, otros autores, que utilizaron estrategias como la música, entorno relajado, meditación, distracción visual y auditiva, etc., estos no lograron revelar un impacto significativo en los niveles de presión arterial en procedimientos endoscópicos (3,6) . Un hallazgo interesante (29) que podría explicar estas diferencias, señala que los cambios de presión arterial pueden ocurrir por diferentes tipos de anestesia y/o medicamentos, que comparado con el pabellón de procedimientos endoscópicos del hospital en estudio, el tipo de anestesia se mantuvo constante y no se administraron sedantes, por lo tanto, los resultados se debieron al acompañamiento significativo que tuvo el paciente en la etapa intra y postprocedimiento. Con respecto a los parámetros de la frecuencia cardiaca, los resultados fueron bastante claros al informar que hubieron diferencias significativas entre los grupos en la etapa pre (p= 0,003) y postprocedimiento (p= 0,0003), lo que es consistente con estudios anteriores (1,9,30) , pero contrario a otros que no lograron reportar cambios o diferencias significativas en estudios endoscópicos (3,6) .…”
Section: Pruebas Deunclassified
“…Significant oscillations of periprocedural blood pressure (BP) in patients with acute ischemic stroke (AIS) treated with mechanical thrombectomy (MT) are now considered to be a common finding ( 1 ). Accumulating evidence indicates that they may influence treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%